PENGARUH PEMASARAN INTERNAL TERHADAP KEPUASAN PELANGGAN INTERNAL PERUSAHAAN PADA PDAM TIRTA MAYANG KOTA JAMBI - Laila Farhat; Usdeldi Usdeldi (Ekonomis: Journal of Economics and Business, 2017)
This study aimed is to analyze the effect of Internal Marketing to Internal Customer Satisfaction Company On PDAM TirtaMayang city of Jambi, The population is PDAM TirtaMayang Employees, it is selected randomly as many as 72 people. Results were statistically demonstrated that the Internal Marketing consists of five dimensions together affect the internal customer satisfaction on PDAM TirtaMayang determinant coefficient Jambi with 61.00 percent. Partially there are two variables: the recruitment and empowerment of the five dimensions that have a positive and significant effect, while for the other three variables, is not significant. And the most influential variable is the variable employee empowerment. In addition, given the influence of the independent variables together against internal customer satisfaction on the company PDAM TirtaMayang Jambi City by 61.00 percent, 39.00 percent of course there are still other variables beyond the variables that affect the company's internal customer satisfaction on the taps TirtaMayang Jambi City that need to be investigated further.Keywords: Internal Marketing, Internal Customer Satisfaction.